Pendampingan Pengajaran Metode Tajwid Maisura pada Peserta Didik Kelas IX MTs Al-Barkah Sukabumi - Wijaya, Subur; Yusron Shidqi, Muhammad; Hamzah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This article aims to analyze the implementation of Maisura method teaching guidance for ninth-grade students at MTs Al-Barkah. The research method used is qualitative with a PAR (Participatory Action Research) approach. Data was obtained through interviews, documentation, and direct field research. This study found that ninth-grade students at MTs Al-Barkah experienced an improvement in the quality of their Quran reading after following the Maisura method teaching guidance. The Maisura method teaching by the Community Service Team (PkM) of STKQ Al-Hikam was conducted in a flexible and creative way, where the material was delivered in a relaxed and enjoyable manner to create a non-rigid learning atmosphere. The results of this study indicate that the Maisura method, which has been considered more suitable for advanced learners, can be used for beginners with some adjustments. The strategy implemented is simplifying the material and using creative analogies so that students can understand the concept of tajwid without feeling burdened by overly complex theory.